1978
DOI: 10.1002/pssa.2210460213
|View full text |Cite
|
Sign up to set email alerts
|

On the diffusion process of point defects in the stress field of edge dislocations

Abstract: An analytic solution of the time‐dependent diffusion equation for point defects in the stress field of a straight edge dislocation is given taking into account the elastic interaction due to the first‐order size‐effect. Modified Bessel functions determine the steady‐state contribution to the defect concentration whereas the time‐dependent part is governed by modified Mathieu functions. The results are applied to the calculation of the dislocation bias for interstitial absorption playing an important role with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…In the case of pure straight dislocations, it has been shown [9] that, without elasticity, the present model gives results in good agreement with the Wiedersich solution. Further comparison showed that, when taking into account elasticity, the Rauh and Simon solution [5] underestimates the sink strength and the elastic bias at dislocation densities which can be encountered in real irradiated materials. This previous validation work allows to apply the model to dislocation loops.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of pure straight dislocations, it has been shown [9] that, without elasticity, the present model gives results in good agreement with the Wiedersich solution. Further comparison showed that, when taking into account elasticity, the Rauh and Simon solution [5] underestimates the sink strength and the elastic bias at dislocation densities which can be encountered in real irradiated materials. This previous validation work allows to apply the model to dislocation loops.…”
Section: Resultsmentioning
confidence: 99%
“…In the models described by Nichols [1], the effect of the dislocation stress field on PD diffusion was neglected. As the elastic drift is thought to be one of the driving forces for swelling in irradiated fcc crystals [2,3], the elastic interaction between the dislocation line and PDs has been first taken into account assuming that the crystal properties were isotropic with PDs modelled as dilatation centres [4][5][6][7][8][9]. More recent works considered the influence of the anisotropy of the crystal and of the PD shape in its equilibrium [10] and saddle point configuration [11][12][13][14][15][16] on sink strength.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the diffusion of vacancies within the heterogeneous stress field around an edge dislocation core has been treated in [19] using Bessel functions. In contrast, boundary value problems involving coupled diffusion-stress phenomena have been solved analytically using Cosserat spectrum theory in [15].…”
mentioning
confidence: 99%
“…Rauch and Simon [3] have found an analytical solution of Eq. (8) subject to the exact boundary condition (10), which yields the following expression for the PD current into a dislocation:…”
Section: Bias Of a Straight Dislocationmentioning
confidence: 99%
“…In this regard, the point defect diffusion into a straight dislocation and a dislocation loop with account of its stress field has been a subject of numerous investigations [1][2][3][4][5][6][7][8][9]. Most of the work is based on the analysis of the size effect, which is the principle elastic interaction between point defects and dislocations in most metals [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%